Isolamento, caracterização taxonômica e aplicação de leveduras no processo de fabricação de cervejas personalizadas - Andrion, Bruno Cardoso (2022)
The brewing market has been expanding with important demands aimed at improving the quality of the drink. One of the alternatives to improve the process would be the identification of yeast strains with unique organoleptic characteristics. Thus, this study aimed to understand the dynamics of yeast succession throughout the production chain of a small microbrewery in a city in the interior of São Paulo, aiming to create a yeast bank that can be used to identify strain customized. And as the specific aimed, it was: a) to identify the diversity of yeasts participating in the production process in a microbrewery; b) to relate this sensorial contribution with the territorial characteristics that are present in that brewery; c) to identify and reproduce Brazilian yeast(s) with potential for the beverage industry and the assembly of a personalized microorganism bank that can be used for the production of personalized beers; d) to verify the productive efficiency and sensory characteristics of beers produced with the isolates; and e) to identify, through the study of the gene expression of these yeasts, possible alterations in metabolic pathways that are of interest to the brewing industry and develop these yeasts to contribute to the production process. For this purpose, the present study was divided into five stages: (I) Collection and propagation of Yeasts in 13 production points encompassing the entire production process; (II) Analyzes and creation of the yeast bank based on morphology (III) Characterization of the bank by sequencing the ITS region of the ribosomal DNA (IV) Selection of yeasts with productive potential and (V) Brewing with selected yeast in scale pilot. So far, topics I to III have been completed. 119 colonies were tested due to their morphological characteristics, which after sequencing were grouped into eight different species of the order Saccharomycetales (Candida tropicalis; Diutina rugosa, Hanseniaspora pseudoguilliermondi; Kazachstania yasuniensis; Pichia Kudriavzeivii; Pichia myanmarensis; Saccharomyces cerevisiae; Wickerhamomyces anomalus), which were organized in genetic proximity in 2 stages (pre and post fermentation); Of the strains belonging to the species S. cerevisiae, 5 colonies were subjected to growth and fermentation tests at different temperatures and malt extract concentrations, the 3 best being selected for micro-scale beer production for evaluation in a sensory test by trained sensory panel. Among these 5 candidates we selected the GP2 yeast, it was chosen due to its sensory characteristics very different from the standard and with good fermentative performance. During fermentation, samples was collected for the evaluation of gene expression by real-time PCR (qPCR) of genes related to important metabolic pathways related to sugar consumption, ethanol production and aromas). We hope that the results of this work can identify new Brazilian yeasts that can produce beers with new aromas and flavors, in addition to making the process more competitive and with lower production costs. It was possible to verify a diversity of yeasts within a microbrewery, which were obtained from the inputs to the end of the production process. With this selection, it was possible to identify and to select strains with productive potential that showed growth characteristics, alcohol formation and aromatic compounds with interest for the brewing industry. In addition, it was possible to identify the metabolic pathways used by the selected strains, which it is important for future studies regarding the development of yeasts through crosses and selections or domestication of wild yeasts of interest.